2010
DOI: 10.5039/agraria.v5i3a795
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade do feijão-caupi cv BR 17 Gurguéia inoculado com bactérias diazotróficas simbióticas no Piauí

Abstract: Produtividade do feijão-caupi cv BR 17 Gurguéia inoculado com bactérias diazotróficas simbióticas no Piauí RESUMOO feijão-caupi é de grande importância para as regiões Norte e Nordeste do Brasil pela sua adaptabilidade a condições edafo-climáticas e por ser uma das principais fontes de proteína para as populações dessas regiões. Assim, neste trabalho objetivou-se selecionar cepas de bactérias diazotróficas simbióticas para serem utilizadas como inoculantes para a cultura do feijão-caupi (Vigna unguiculata (L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
3
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 14 publications
3
20
3
13
Order By: Relevance
“…Costa et al (2011) found that inoculation with INPA 03-11B promoted similar yields to that of N fertilization, in Bom Jesus, state of Piauí, with productivity of up to 1,604 kg ha -1 . Almeida et al (2010) in an experiment carried out at Teresina, state of Piaui, reported a grain yield of 1,637 kg ha -1 for the cultivar BR 17 Gurguéia inoculated with the strain BR 3267, and of 1,823 kg ha -1 when inoculated with the strain BR 3262, a 24.6 and 38.9% increase, respectively, compared to that of the control treatment.…”
Section: Dry Matter Of Shoots ------------------(Mg Per Plant)-------mentioning
confidence: 97%
See 1 more Smart Citation
“…Costa et al (2011) found that inoculation with INPA 03-11B promoted similar yields to that of N fertilization, in Bom Jesus, state of Piauí, with productivity of up to 1,604 kg ha -1 . Almeida et al (2010) in an experiment carried out at Teresina, state of Piaui, reported a grain yield of 1,637 kg ha -1 for the cultivar BR 17 Gurguéia inoculated with the strain BR 3267, and of 1,823 kg ha -1 when inoculated with the strain BR 3262, a 24.6 and 38.9% increase, respectively, compared to that of the control treatment.…”
Section: Dry Matter Of Shoots ------------------(Mg Per Plant)-------mentioning
confidence: 97%
“…However, the rather insignificant productive response of cowpea genotypes to inoculation resulted in low diffusion of the technology among farmers in the Semiarid region. Nevertheless, over the past few years, researches have shown that some rhizobial strains, with high agronomic efficiency, can increase the productivity of cowpea in the region (Almeida et al, 2010;Costa et al, 2011;Fernandes Júnior et al, 2012;Freitas et al, 2012;Ferreira et al, 2013;Alcantara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soares et al (2006), working with cowpea cultivar BR-14 Mulato in Perdões, Minas Gerais, reported yields of 949 and 950 kg ha -1 in treatments inoculated with the strains INPA 03-11B and UFLA 03-84, respectively, which were similar to the control treatments with mineral N and higher than uninoculated controls without N, which yielded only 341.80 kg ha -1 . Almeida et al (2010), in a trial conducted in the city of Teresina, Piauí, using the cowpea cultivar BR 17 Gurguéia inoculated with the strains INPA 03-11B, BR 3267 and BR 3262, also reported yields similar to the control treatment with mineral N and yields higher than the uninoculated control without N.…”
Section: Introductionmentioning
confidence: 92%
“…A FBN é reconhecidamente eficiente em feijão-caupi, que quando bem nodulado, pode crescer independente de outras fontes de N e atingir altos níveis de produtividade (SOARES et al, 2006;ALMEIDA et al, 2010;COSTA et al, 2011). Entretanto, a nodulação e a FBN são influenciadas por diversos fatores edafoclimáticos, dentre os quais se destaca a disponibilidade de nutrientes (GUALTER et al, 2008;BONILLA;BOLAÑOS, 2009;SILVA et al, 2010).…”
Section: Introductionunclassified